The determination of performance measures by using a balanced scorecard framework - Irem Kefe (Foundations of Management, 2019)
The aim of this study was to determine the contributions of the balanced scorecard (BSC) methods to identify the relationship between the objectives and activities and examine how the BSC should be formed in a manufacturing company. The BSC framework was examined via a case study in a yarn manufacturing company. The activities to be carried out by the company to achieve its objec-tives and how the appropriate measures are determined in evaluating the contribution of the activities to the achievement of objectives are explained under the BSC approach. The BSC implementation and adaptation have facilitated in a family owned company because of its fast decision-making process. Ob-jectives are made clear in accordance with the company's strategy and causal relationship between ob-jectives and activities are linked by the strategy map. The BSC implementation shows that financial measures are not enough to evaluate the effects of all the activities on the objectives in a company. The cooperation between departments in the company and the efficiency of corporation meetings in-creases. The meetings have become more result-oriented due to clarifying objectives and responsibility of individual levels.
Keywords: M10; M4; 650; balanced scorecard; performance measures; strategy maps; strategic planning; manufacturing